The Optimum Design of 3D Sensor for Electrical Capacitance Volume-Tomography (ECVT) - Marlin Ramadhan Baidillah; W. Warsito; Muhammad Mukhlisin (Jurnal Matematika & Sains, 2011)
A tomography system based on capacitance measurement is attempts to map dielectric permittivity of materials. The measured capacitance of the pair between source and detector is dependent to surface area enclosing detector electrode. Imaging a three-dimensional object requires sensitivity matrix with three-dimensional variation, especially in axial (z-axis) direction to differentiate the depth along the sensor length. Therefore, the fundamental concept of electrical capacitance sensor design for 3-D volume imaging is to distribute equally electrical field intensity all over three-dimensional space. In ECVT, due to the weakness of the electrical field, the capacitance measurement that generates information simultaneously of the volumetric properties can be made using arbitrary shapes of sensors and vessels. In this study, we designed and analyzed the 3-D sensitivity matrix for 4 different geometry sensors: hexagonal, rectangular, trapezoid and triangular. The comparisons of sensitivity distribution showed that hexagonal sensor gives relatively more uniform sensitivity variation in both the radial and axial directions. Keywords: ECVT, 3-D volume imaging, 3-D sensitivity matrix, 3-D sensor capacitance.Â  Desain Optimum Sensor 3D untuk Tomografi Volum Kapasitansi Listrik Abstrak Sebuah sistem tomografi yang berdasarkan pengukuran kapasitansi diterapkan untuk pemetaan permitivitas bahan dielektrik. Kapasitansi pasangan sumber dan detektor yang diukur tergantung pada luas permukaan elektroda detektor. Pencitraan sebuah objek tiga dimensi memerlukan matriks sensitivitas tiga dimensi, terutama dalam arah aksial (sumbu z) untuk membedakan variasi sepanjang sensor. Oleh karena itu, konsep mendasar dari desain sensor kapasitansi listrik untuk pencitraan 3-D volume adalah mendistribusikan intensitas medan listrik yang sama besar di seluruh ruang tiga dimensi. Dalam ECVT, karena medan listrik yang lemah, pengukuran kapasitansi yang menghasilkan informasi secara simultan dari sifat volumetrik dapat dibuat dengan menggunakan bentuk sensor dan tabung yang sebarang. Dalam studi ini, kami merancang dan menganalisis matriks sensitivitas 3-D untuk 4 geometri sensor yang berbeda: heksagonal, segi empat, trapesium, dan segitiga. Perbandingan distribusi sensitivitas menunjukkan bahwa sensor heksagonal memberikan variasi sensitivitasÂ  lebih seragam baik dalam arah radial dan aksial. Kata kunci: ECVT, Pencitraan 3-D volume, Matriks sensitivitas 3-D, Sensor kapasitansi 3-D.